Bioflocculant producing-bacteria from tapioca waste water were characterized. Two bacterial isolates i.e. LT-5 and LT-6 isolates had high flocculation activity, with activity of 68.92 and 71.38% respectively. The flocculation activity of LT-5 isolate increased at pH 2.0-4.0 (acidic condition), however the activity of LT-6 increased at pH 6.0-8.0 (neutral). Addition of 0.05% of AlCl3 as cation was the most effective and had important role in flocculation activity. Based on the morphological prope - . SURYANI; LAKSMI AMBARSARI; I MADE ARTIKA; HARTUTIK EKA SUSANTI (Bogor Agricultural University, Indonesia, 2011)
Bioflocculant producing-bacteria from tapioca waste water were characterized. Two bacterial isolates i.e. LT-5 and LT-6 isolates had high flocculation activity, with activity of 68.92 and 71.38% respectively. The flocculation activity of LT-5 isolate increased at pH 2.0-4.0 (acidic condition), however the activity of LT-6 increased at pH 6.0-8.0 (neutral). Addition of 0.05% of AlCl3 as cation was the most effective and had important role in flocculation activity. Based on the morphological properties, LT-5 isolate was identified as Chromobacterium violaceum and LT-6 isolate was identified as Citrobacter koseri.